2019
DOI: 10.1021/acs.inorgchem.9b02044
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Complexes of Highly Rigid, Open-Chain Ligands Containing a Cyclobutane Ring in the Backbone: Decreasing Ligand Denticity Might Enhance Kinetic Inertness

Abstract: In an effort of exploring novel ligand scaffolds for stable and inert lanthanide complexation in MRI contrast agent research, three chiral ligands containing a highly rigid (1S,2S)-1,2-cyclobutanediamine spacer and different number of acetate and picolinate groups have been efficiently synthesized. Potentiometric studies show comparable thermodynamic stability for the Gd 3+ complexes formed with either the octadentate (L3) 4 bearing two acetate or two picolinate groups or the heptadentate (L2) 4 analogue bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…However, they agree well with the relaxivity of the rigid, monohydrated [Gd­(CBDDADPA)­(H 2 O)] − complex, r 1p = 5.6 mM –1 s –1 (Scheme S1). The r 1p values of [Gd­(FENTA)] − decrease by increasing the temperature from 25 to 37 °C at both magnetic fields, indicating that the relaxivity is controlled by fast rotation, as it has earlier been reported for several low molecular weight Gd­(III) complexes . To get information on the relaxivity of the [Gd­(FENTA)] − complex in human serum, we performed measurements for both field strengths at 25 and 37 °C.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…However, they agree well with the relaxivity of the rigid, monohydrated [Gd­(CBDDADPA)­(H 2 O)] − complex, r 1p = 5.6 mM –1 s –1 (Scheme S1). The r 1p values of [Gd­(FENTA)] − decrease by increasing the temperature from 25 to 37 °C at both magnetic fields, indicating that the relaxivity is controlled by fast rotation, as it has earlier been reported for several low molecular weight Gd­(III) complexes . To get information on the relaxivity of the [Gd­(FENTA)] − complex in human serum, we performed measurements for both field strengths at 25 and 37 °C.…”
Section: Resultssupporting
confidence: 73%
“…DFT predicted similar Gd-N phenanthroline distances (2.64 and 2.67 Å) and bite-angle of the phenanthroline moiety (61.2°) compared to those reported for a bis­(phenanthroline)-gadolinium­(III) complex (2.60 and 2.57 Å and 63.5°) . The Gd-N amine distances are calculated to be 2.67 and 2.73 Å, which are shorter than those of highly rigid open-chain gadolinium­(III) complexes possessing a cyclobutene ring in the ligand backbone . Thus, it is reasonable to assume that the rigid phenanthroline backbone pre-organizes the coordination cavity and, as a result, enhances the inertness of the complex.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Encouraged by the results, the Cu 2+ transmetallation was also evaluated as the Cu 2+ was involved in many physiological processes and empirically displayed strong coordinating capability. [ 27 ] As implied in Figure 3g, the T 1 of fe Gd‐N x C maintained well for two months, on the contrary, Gd‐DTPA displayed an obvious Gd 3+ leakage, namely, the initial T 1 value of Gd‐DTPA (0.95 s) quickly reduced to 0.36 s in the following days. These results suggested that the Gd 3+ in fe Gd‐N x C was more resistant to dissociation under physiological conditions than that of Gd‐DTPA.…”
Section: Resultsmentioning
confidence: 91%
“…This approach provided a high degree of accuracy in the prediction of Gd-O water distances and the localization of spin density at the O nuclei of the water molecule. 18,42,43 Moreover, dispersion corrections were incorporated into our DFT calculations for a more accurate prediction of inter-and intramolecular interactions. Details are provided in the Experimental section.…”
Section: Dft Calculationsmentioning
confidence: 99%